THE IMPORTANCE OF UTILIZING LOCATIVE SEMANTICS - Zubaydova Nilufar Nematillayevna, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article devoted to open the theme the importance of utilizing locative semantics. On the other hand, ways of expressing locative adessive elements in English and Uzbek languages were comperatively studied. Key words: separative case, locative ablative, adessive elements, semiconductor, plausible bound, approximative mode, the cofinal, the coinitial